Strontium Sulfite: A New pH-Responsive Inorganic Nanocarrier to Deliver Therapeutic siRNAs to Cancer Cells - Md. Emranul Karim; Jayalaxmi Shetty; Rowshan Ara Islam; Ahsanul Kaiser; Athirah Bakhtiar; Ezharul Hoque Chowdhury (MDPI AG, 2019)
Inorganic nanoparticles hold great potential in the area of precision medicine, particularly for treating cancer owing to their unique physicochemical properties, biocompatibility and improved pharmacokinetics properties compared to their organic counterparts. Here we introduce strontium sulfite nanoparticles as new pH-responsive inorganic nanocarriers for efficient transport of siRNAs into breast cancer cells. We employed the simplest nanoprecipitation method to generate the strontium sulfite nanoparticles (SSNs) and demonstrated the dramatic roles of NaCl and d-glucose in particle growth stabilization in order to produce even smaller nanosize particles (Na-Glc-SSN) with high affinity towards negatively charged siRNA, enabling it to efficiently enter the cancer cells. Moreover, the nanoparticles were found to be degraded with a small drop in pH, suggesting their potential capability to undergo rapid dissolution at endosomal pH so as to release the payload. While these particles were found to be nontoxic to the cells, they showed higher potency in facilitating cancer cell death through intracellular delivery and release of oncogene-specific siRNAs targeting ros1 and egfr1 mRNA transcripts, than the strontium sulfite particles prepared in absence of NaCl and d-glucose, as confirmed by growth inhibition assay. The mouse plasma binding analysis by Q-TOF LC-MS/MS demonstrated less protein binding to smaller particles of Na-Glc-SSNs. The biodistribution studies of the particles after 4 h of treatment showed Na-Glc-SSNs had less off-target distribution than SSNs, and after 24 h, all siRNAs were cleared from all major organs except the tumors. ROS1 siRNA with its potential therapeutic role in treating 4T1-induced breast tumor was selected for subsequent in vivo tumor regression study, revealing that ROS1 siRNA-loaded SSNs exerted more significant anti-tumor effects than Na-Glc-SSNs carrying the same siRNA following intravenous administration, without any systemic toxicity. Thus, strontium sulfite emerged as a powerful siRNA delivery tool with potential applications in cancer gene therapy.